Analysis of fires and rescue work in Lithuania/Gaisrų ir gelbėjimo darbų Lietuvoje analizė - Čyras, Petras; Griškevičius, Mecislavas (Journal of Civil Engineering and Management, 2001)
In 1999, there were 14 002 fires in Lithuania. Their losses reached 24 mill Litas. Comparing with 1998, the number of fires increased by 50,2% and loss—10.4%. Fires destroyed 1006 buildings, 215 vehicles, 4,4 tons of grain and other technical cultures. In 1999, 202 inhabitants died during fires in Lithuania, 13 including children; 214 inhabitants were wounded. For 10 000 inhabitants were 37.8 fires. In 1999 there were 10.11% arsons in Lithuania. The most of fires were in open places, in forests, in meadows and peat bogs. 35% of fires occurred in dwelling sector. The essential fire causes are: careless contact with fire (49.66%), violation electrical equipment rules (11.06%), naughty children (9.11%). 4412 duty persons are working in Lithuanian fire and rescue service. Fire and rescue service has 44 branches in the cities. 430 duty persons guard three the most important industrial objects. 202 firemen brigades are financed from the magistrate budgets. They include 2225 staff. In 1999 State inspectorate for fire prevention worked effectively. New statute, instruction of work organisation was prepared, all-important industrial objects were inspected. The strategical work of branches was improved. 28% of fires were eliminated faster than in 15 minutes, the number of fires which elimination takes more than 2 hours decreased. In 1999, Lithuanian fire and rescue brigades made 5781 rescue works. 800 of them were car accidents, 305 – search for drowned men, and 9 people were saved in the water. Diving training section was established in the firemen training centre. Officials raise their qualification constantly. 1301 officials have a qualification category. In 1999, 202 privates and 18 officers were trained in the firemen training centre, 980 privates and 206 officers were requalified. 102 officials were retrained with the help of Norway firemen association. 24 Lithuanian officials raised their qualification in Sweden and 22 in Denmark. 51 divers were trained and 74 divers got their rating. Priorities of work: – further reorganisation of Fire and rescue service; – development of legal regulations; – improvement of fire-fighters training and further qualification raising process; – widening of rescue works spectrum; – better supply of technical equipment of Fire brigades. Article in Lithuanian. First Published Online: 30 Jul 2012